Quantifying the increased risk of illness in malnourished children: a global meta-analysis and propensity score matching approach - Mukhtar A. Ijaiya; Seun Anjorin; Olalekan A. Uthman (BMC, 2024)
Abstract Background Childhood morbidity and mortality continue to be major public health challenges. Malnutrition increases the risk of morbidity and mortality from illnesses such as acute respiratory infections, diarrhoea, fever, and perinatal conditions in children. This study explored and estimated the magnitude of the associations between childhood malnutrition forms and child morbidity. Methods We performed an individual participant data (IPD) meta-analysis and employed propensity score matching to examine crude (unadjusted) and adjusted associations. Our analysis utilized demographic and health datasets from surveys conducted between 2015 and 2020 in 27 low- and middle-income countries. Our objective was to quantify the risk of morbidity in malnourished children and estimate the population-attributable fraction (PAF) using a natural experimental design with a propensity score-matched cohort. Results The IPD meta-analysis of child morbidity across three childhood malnutrition forms presented nuanced results. Children with double-burden malnutrition had a 5% greater risk of morbidity, which was not statistically significant. In contrast, wasted children had a 28% greater risk of morbidity. Overweight children exhibited a 29% lower risk of morbidity. Using the matched sample, children with double-burden malnutrition and overweight children had lower morbidity risks (1.7%, RR: 0.983 (95% CI, 0.95 to 1.02) and 20%, RR: 0.80 (95% CI, 0.76 to 0.85), respectively), while wasting was associated with a 1.1 times (RR: 1.094 (95% CI, 1.05 to 1.14)) greater risk of morbidity. Eliminating double-burden malnutrition and wasting in the four and seven countries with significant positive risk differences could reduce the child morbidity burden by an estimated average of 2.8% and 3.7%, respectively. Conclusions Our study revealed a correlation between specific childhood malnutrition subtypes-double-burden malnutrition and wasting-and increased risks of morbidity. Conversely, overweight children exhibited a lower risk of immediate morbidity, yet they may face potential long-term health challenges, indicating the necessity for nuanced approaches to childhood nutrition.